2015 National Psoriasis Foundation Research Symposium: Emerging Paradigms and Best Practices in Psoriatic Disease Research and Care. Issue 1 (December 2015) - Leavitt, Melissa; Rybacki, Laurissa; Siegel, Michael
The National Psoriasis Foundation (NPF) Research Symposium was held in San Francisco on July 23 to 25, 2015. Bringing together basic scientists, physicians, and psoriatic disease patients, the Symposium's scientific sessions offered an overview of milestones in the field of psoriatic disease and introduced new paradigms for research and clinical care. As many lectures emphasized, central to these new paradigms is a push to progress beyond association and observational studies to gain a better understanding of the functional mechanisms involved in disease pathogenesis and treatment. Looking ahead, the themes that emerged throughout the Symposium will help guide the future of the NPF's research programs.